Antibacterial activity of plant extracts from northwestern Argentina - Soberon, Jose Rodolfo (2007)
To determine the antibacterial and cytotoxic activities of aqueous and ethanolic extracts of northwestern Argentinian plants used in folk medicine. To compare the mentioned activities with those of five commercial antibiotics. To identify the compounds responsible for the antibacterial activity. Methods and Results: Plant extracts were prepared according to traditional uses in northwestern Argentina. Antibacterial activity was assayed by agar dilution in Petri dishes and broth dilution in 96-well plates. Lethal dose 50 (LD50) was determined by the Artemia salina assay. Phytochemical analysis was performed by sample adsorption on silica gel, thin-layer chromatography (TLC), bioautography and UV-visible spectra. The results showed that Tripodanthus acutifolius aqueous extracts have lower minimal inhibitory concentrations (MIC) (502 and 506 ìg of extracted material (EM) per ml for infusion and decoction, respectively) than cefotaxim MIC (640 ìg . ml-1) against Acinetobacter freundii (303). These data were lower than their LD50. Tripodanthus acutifolius tincture showed lower MIC (110 ìg of EM per ml) and minimal bactericidal concentration (MBC) (220 ìg of EM per ml) than cefotaxim (MIC and MBC of 320 ìg . ml-1) for Pseudomonas aeruginosa. This extract also showed a MIC/MBC of 110/220 ìg of EM per ml, lower than  oxacillin (MIC/MBC of 160/220 ìg ml-1) for Staphylococcus aureus (ATCC 25923). The cytotoxicity of all extracts were compared with that of commercial antibiotics. Rutin (3,3´,4´,5,7-pentahydroxyflavone 3-â-rhamnosilglucoside), iso-quercitrin (3,3´,4´,5,7-pentahydroxyflavone 3- â -glucoside) and a terpene would be partially responsible for the antibacterial activity of T. acutifolius infusion. Conclusions: Tripodanthus acutifolius extracts had the ability to inhibit bacterial growth. The antibacterial activity differs with the applied extractive method, and it could be partially attributed to glycoflavonoids. This paper contributes to the knowledge of antibacterial capacity of plants from northwestern Argentina. Significance and Impact of the Study: These antibacterial activities support further studies to discover new chemical structures that can contribute to alleviate or cure some illnesses.